Tanggung Jawab Negara dalam Hukum Internasional: Pemenuhan Komitmen COP26 oleh Indonesia - Fillo Sofia, Tasya; Azahra Nabila Nasution, Shafira; Bellin, Adhika Adyatma; Septaria, Ema (Jurnal Hukum Positum, 2024)
Climate change is a global threat that requires international cooperation. The commitments agreed upon in COP26 have become a significant milestone in the efforts to control the impacts of climate change, including for Indonesia as one of the largest emitters. This article analyzes the state’s responsibility in fulfilling international legal obligations, particularly regarding the implementation of Indonesia’s COP26 commitments, using a normative legal research method. This approach examines the applicable legal norms, including international agreements and national regulations, in the context of the implementation of state obligations. The results show a violation of Indonesia’s COP26 Agreement commitments. Indonesia has committed to reduce its carbon emissions, but in reality, Indonesia’s dependence on coal is the main cause of carbon emissions and deforestation policies. The conclusion of this research is the importance of consistent law enforcement and regulatory strengthening, supported by international cooperation, in helping Indonesia meet its COP26 commitments to address climate change.